Cu2O nanoparticles supported on carbon nanofibers as a cost-effective and efficient catalyst for RhB and phenol degradation. Issue 18 (22nd August 2017) - Liu, Yongkun; Huang, Qin; Jiang, Guohua; Liu, Depeng; Yu, Weijiang
Abstract: Abstract : In this work, the hybrid carbon nanofibers (Cu2 O/CNFs) containing cuprous oxide (Cu2 O) nanoparticles were prepared by a convenient electrospinning method and following a carbonization treatment. The morphology, composition, and microstructure of the Cu2 O/CNFs were characterized by scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray diffractometer. The as-prepared Cu2 O/CNFs exhibited a stronger absorption in the range of 250–700 nm. The band gap energy of the Cu2 O/CNFs was estimated to be 2.0 eV. Due to the synergistic effect between photocatalytic activity of Cu2 O and excellent adsorption capacity of CNFs, the obtained Cu2 O/CNFs exhibited excellent photocatalytic activity for degradation of rhodamine B (RhB) and phenol. The possible mechanism for degradation of RhB and phenol degradation were also discussed. The resultant hybrid carbon composites offer the significant advantages, such as low dosage, high catalytic activity, easy recycling, and excellent stability. We hope that the resultant hybrid composite Cu2 O/CNFs could be applied as catalytic materials for further application in the future.